AB0305 Influence of Drug Levels during The First Anti-Tnf Therapy on The Clinical Response To A Second Biologic in Rheumatoid Arthritis Patients. (15th July 2016) - Plasencia-Rodriguez, C.; Pascual-Salcedo, M.D.; Bonilla, G.; Navarro-Compán, V.; Martinez-Feito, A.; Diego, C.; Villalba, A.; Peiteado, D.; Nuño, L.; Martin-Mola, E.; Balsa, A.
Abstract : Background: The anti-tumor necrosis factor (anti-TNF) therapy has shown to be effective in rheumatoid arthritis (RA). Recent publications have shown the association between drug levels (DL) and clinical response to the anti-TNF therapies. For now it is not clear if the DL monitoring to the 1st anti-TNF in patients who discontinued due to inefficacy, can be useful to evaluate the clinical efficacy to the 2nd anti-TNF. Objectives: To evaluate in a RA cohort (who stopped to the 1st anti-TNF due to inefficacy), the influence of the presence/absence of DL [infliximab (Ifx) y adalimumab (Ada)] at discontinuation, on the clinical response to the 2nd anti-TNF during the 1st year of therapy. Methods: Seventy seven out of 182 RA patients who discontinued the Ifx or Ada therapy were recruited. All these patients dropped out the first anti-TNF due to inefficacy and switched to a 2nd anti-TNF (48 patients: 2 with Ifx, 4 with Ada, 40 with etanercept and 2 with certolizumab) or other biologics (OB) different to anti-TNF (29 patients: 17 with rituximab, 6 with tocilizumab and 6 with abatacept). Clinical activity was measured by DAS28 and clinical improvement by Delta-DAS28 adjusted to baseline clinical activity (baselineDAS-DAS (24weeks or 52weeks)/baselineDAS) at baseline, 24 weeks (24w) and 52 weeks (52w). DL were measured prior to drug administration at 24w and 52w by ELISA. Results: Of the 77 RA patients, 82% (63/77) were women and the mean disease duration was 21±13 years. At the end of the 1st antiTNF, 54/77 (70%) had undetectable DL and 23/77 (30%) had detectable DL. At w24 of the 2nd biologic, patients treated with OB tended to be less active than patients treated with a 2nd anti-TNF but these differences were not significant at w52 ( DAS28 at w24: 3.5±1.3 with OB vs 4.1±1.1 wirh 2nd anti-TNF, p=0.053; Delta-DAS28 at w24: 0.3±0.3 with OB vs 0.2±0.3 with 2nd anti-TNF, p=0.326; DAS28 at w52: 3.3±1.2 with OB vs 3.8±1.1 with 2nd anti-TNF, p=0.166; Delta-DAS28 at w52: 0.3±0.2 with OB vs 0.2±0.3 with 2nd anti-TNF, p=0.501). Patients with undetectable DL to first anti-TNF treated with a 2nd anti-TNF had better clinical response during the first year of therapy ( DAS28 at w24: 3±1.1 with non DL vs 4.3±1.2 with DL, p=0.004; Delta-DAS28 at w24: 0.3±0.3 with non DL vs 0.2±0.3 with DL p=0.074; DAS28 at w52: 2.9±1.1 with non DL vs 4±1.2 with DL, p=0.015; Delta-DAS28 at w52: 0.4±0.2 with non DL vs 0.2±0.3 with DL, p=0.210). However, no differences in the clinical activity were observed between patients with undetectable or detectable DL who switched to OB ( DAS28 at w24: 4.4±1.4 with non DL vs 3.8±1 with DL, p=0.247; Delta-DAS28 at w24: 0.2±0.2 with non DL vs 0.2±0.2 with DL, p=0.382; DAS28 at w52: 4.1±1.2 with non DL vs 3.5±0.7 with DL, p=0.122; Delta-DAS28 at w52: 0.2±0.2 with non DL vs 0.3±0.1 with DL, p=0.376). Conclusions: In our cohort of RA patients with inefficacy to the 1st anti-TNF, a high proportion of patients discontinued the therapy with undetectable DL. The DL monitoring during the 1st anti-TNF seems to be a useful tool to define what patients have a better clinical response to the 2nd anti-TNF, although this effect does not influence on those patients who switch to OB. Disclosure of Interest: None declared